Health service use of Australian unemployment and disability benefit recipients: a national, cross-sectional study - Alex Collie; Luke Sheehan; Ashley McAllister (BMC, 2021)
Abstract Background Healthcare is funded and delivered separately from income support programs such as unemployment and disability benefits. Greater understanding of the health service use (HSU) of benefit recipients would support more effective design and delivery of health and income support programs. This study aimed to characterise the HSU of disability and unemployment benefit recipients relative to people earning wages, while controlling for personal, household and health-related factors associated with HSU in benefit recipients. Methods A cross-sectional national survey of 9110 working age Australian adults in three groups: (1) 566 receiving the disability support pension (DSP); (2) 410 receiving unemployment benefits; and (3) 8134 earning wages. Outcomes included prevalence and frequency of health professional consultations, hospital attendance and admission in the past 12 months, as well as medication and supplement use in the past 2 weeks. Analyses compared DSP and unemployment benefit recipients to wage earners using prevalence ratios and incident rate ratios, adjusted for predisposing, enabling and need factors that may affect HSU. Results In adjusted regression models, both DSP and unemployment benefit recipients were significantly more likely than wage earners to have consulted psychologists and social workers. DSP recipients also reported a significantly higher prevalence of consultations with General Practitioners (GPs), specialist physicians and podiatrists.. Both groups reported significantly more frequent consultations with GPs and DSP recipients with specialists. No differences were observed between groups for hospital attendance or admission, or supplement use in fully adjusted models, though the DSP group reported more prevalent medication use than wage earners. Inclusion of confounders including self-assessed health, disability severity, health insurance status, and financial resources attenuated the relationship between benefit receipt and HSU, however significant associations were still observed. Conclusions People receiving unemployment and disability insurance benefits use significantly more health services than wage earners. A range of personal and clinical characteristics explained much, but not all, of the association between greater HSU and benefit receipt. Greater coordination between health and income support systems may improve health, reduce HSU and improve work ability in unemployed and working age people.